Simpsons comics supernova. - Groening, Matt; Boothby, Ian; Dorkin, Evan; Pepoy, Andrew; Costanza, John; Novin, Phyllis; Ortiz, Phil; De Carlo, Mike; Nilges, Joey; Ho, Jason; Shum, Howard M.; Davis, Dan W. (HarperCollins Publishers, 2013)
The Springfield family is back in a collection that finds Homer refusing to be separated from his love seat for a whole year and Marge eclipsing newscaster Kent Brockman with her positive outlook on life.